Pre-emptive low-dose ketamine with local anesthesia reduces postoperative morbidity after third molar surgery: A systematic review and meta-analysis. - Shaimaa Mohsen Refahee; Essam Ahmed Al-Moraissi; Ahmed Saleh Yehya Alkhutari (Universidad de Concepción., 2020)
Objective: This review addresses a clinical research question related to lower third molar surgery (L3MS): does the combination of pre-emptive low-dose ketamine with local anesthesia (KLA) reduce postoperative complications compared with local anesthesia (LA) alone? Material and methods: A systematic literature search was performed to identify eligible articles by electronic searches of PubMed, Cochrane Central Register of Controlled Trials, EBSCO Library, Web of Science and grey literature through June 2019 without data or language restrictions. We analyzed all randomized controlled clinical studies (RCTs) comparing use of KLA with use of LA in L3MS regarding pain, swelling, and trismus outcomes. The quality of evidence was rated according to Cochrane's tool for assessing risk of bias. Results: Five RCTs encompassing 230 extraction sites (KLA = 115, LA = 115) were included in this study. The standardized mean difference (SMD) with the 95% confidence interval (CI) was used to synthesize the results. The data show that there were significant differences between the two groups in post-operative pain (SMD -1.464, 95% CI -1.683 to -0.949, p= 0.001) and swelling (SMD -0.450, 95% CI -0.758 to -0.142, p= 0.004, all low quality evidence). However, there was no significant difference in the trismus (SMD -0.754, CI -1.487 to -0.022, p = 0.043, very low quality evidence). Conclusion: The combination of pre-emptive low-dose ketamine with LA significantly decreased pain and swelling within the first 24 hours after L3MS compared with the control group.